Oscillations

Periodic Motion : A motion that repeats itself in equal intervals of time is called periodic motion. It is also called harmonic motion.

Examples. 1. Revolution of earth round the sun or about its own axis, 2. Revolution of moon and other artificial satellites around the earth, 3. Rotation of the electrons round the nucleus of an atom, 4. The motion of pendulum of a clock, 5. Motion of prongs of a tuning fork and 6. Oscillations of a loaded spring.

The two common periodic motions are the simple harmonic motion and uniform circular motion.

Oscillatory Motion : The motion of a particle is oscillatory if it moves back and forth or to and fro about the same path at equal intervals of time.

Examples. 1. Motion of a pendulum, 2. Motion of mass attached to a suspended spring, 3. Motion of atoms in a molecule or a lattice, 4. Motion of particles of the medium through which sound travels, 5. Up and down motion of a floating object on water when waves propagate through it, 6. Motion of prongs of a tuning fork.

All oscillatory motions are periodic in nature but all periodic motions are not oscillatory. For example, revolution of earth round the sun is periodic but not oscillatory and Rotation of the electrons round the nucleus of an atom is periodic but not oscillatory.

Some Definitions:

  1. The smallest time interval in which the motion repeats is called the Time Period (T). It is the time taken for one oscillation.
  2. The number of repetitions of motion that occur per second is called the frequency (f) of the periodic motion. Frequency is equal to the reciprocal of time period. f=1Tf = \frac{1}{T}.
  3. The maximum displacement of a particle from its mean position during an oscillation is called amplitude (A) of oscillation.
  4. Phase: It represents the state of motion of a particle in periodic motion. It is expressed in terms of fraction of period T or the fraction of angle 2π2\pi measured from the instant when the body has crossed the mean position in the positive direction.

Simple Harmonic Motion (SHM)

Topic asked in Applied Physics 2023 (CBCS/NEP) question paper Section B - 3(a).

A particle is said to execute simple harmonic motion if the acceleration of the particle is directly proportional to the displacement of the particle from the mean position and it is directed towards the mean or equilibrium position. Ex. Oscillations of simple pendulum, oscillations of weight attached to spring.

Simple Harmonic Motion

Consider a particle executing oscillatory motion about the mean position (E - M - E) with E as the extreme position and M is the mean position) with amplitude A. Let xx be the displacement of the particle at an instant of time t. A restoring force F acts on the particle to bring it back to its mean position. This force is directly proportional to the displacement.

Mathematically, FxF ∝ x

or

F=kx      —- equation 1F = -kx \; \; \; \text{---- equation 1}

This equation is called as Hooke's law and represents the Restoring force. Where kk is spring constant and its value is depends on stiffness of the spring.

The negative sign indicates that F acts opposite to the direction of motion of the particle.

The acceleration of an object moving with simple harmonic motion can be found by using Hooke's law in the equation for Newton's second law.

F=ma      —- equation 2F=ma \; \; \; \text{---- equation 2}

Comparing equation - 1\text{equation - 1} and equation - 2\text{equation - 2}

ma=kxma = -kx

or

a=(km)x      —- equation 3a = -\left(\frac{k}{m}\right)x \; \; \; \text{---- equation 3}

As a=d2xdt2a= \frac{d^2x}{dt^2}

equation - 3\text{equation - 3} becomes :-

d2xdt2=(km)x\frac{d^2x}{dt^2} = -\left(\frac{k}{m}\right)x

or

d2xdt2+(km)x=0      —- equation 4\frac{d^2x}{dt^2} + \left(\frac{k}{m}\right)x = 0 \; \; \; \text{---- equation 4}

let km=ω2\frac{k}{m} = \omega^2 where ω\omega is called the angular velocity or angular frequency of oscillating particle.

Now, equation - 4\text{equation - 4} becomes :-

d2xdt2+w2x=0      —- equation 5\frac{d^2x}{dt^2} + w^2x = 0 \; \; \; \text{---- equation 5}

equation5equation - 5 is called differential equation of SHM.

Solution of Differential equation of SHM

Displacement of the particle

The differential form of SHM is d2xdt2+w2x=0\frac{d^2x}{dt^2} + w^2x = 0

or

d2xdt2=w2x\frac{d^2x}{dt^2} = -w^2x

Multiplying both the side of this equation by 2dxdt2\frac{dx}{dt}, we get

2dxdtd2xdt2=2dxdtw2x2\frac{dx}{dt}\frac{d^2x}{dt^2} = -2\frac{dx}{dt}w^2x

This equation can be expressed as:- ddt(dxdt)2=w2ddt(x)2\frac{d}{dt}\left(\frac{dx}{dt}\right)^2 = -w^2\frac{d}{dt}\left(x\right)^2

Integrating above equation we get:- (dxdt)2=w2x2+C      —- equation 1\left(\frac{dx}{dt}\right)^2 = -w^2x^2 + C\; \; \; \text{---- equation 1}

Here, C is the constant of integration.

When the displacement is maximum, i.e. x = a, the velocity of the particle dxdt=v=0\frac{dx}{dt}=v=0

Putting this condition in equation 1 , 0=w2a2+C0 = -w^2a^2 + C     or    \; \; or \; \; C=w2a2C=w^2a^2

Now equation - 1 becomes, (dxdt)2=w2x2+w2a2\left(\frac{dx}{dt}\right)^2 = -w^2x^2 + w^2a^2

or (dxdt)2=w2(a2x2)\left(\frac{dx}{dt}\right)^2 = w^2\left(a^2 - x^2\right)     or    \; \; or \; \; dxdt=w(a2x2)      —- equation 2\frac{dx}{dt} = w\sqrt{\left(a^2 - x^2\right)}\; \; \; \text{---- equation 2}

Equation - 2 is also the expression for the velocity of the particle executing SHM.

Rewriting equation - 2 as, dx(a2x2)=wdt\frac{dx}{\sqrt{\left(a^2 - x^2\right)}} = wdt

Integrating this equation, dx(a2x2)=wdt\int\frac{dx}{\sqrt{\left(a^2 - x^2\right)}} = w\int dt

gives,  \; sin1(xa)=wt+φsin^{-1}\left(\frac{x}{a}\right) = wt + \varphi

where φ\varphi is the constant called the initial phase of the particle executing SHM. It is also called epoch.

or

(xa)=sin(ωt+φ)\left(\frac{x}{a}\right) = sin(\omega t + \varphi)     or    \; \; or \; \; x=asin(ωt+φ)x = asin(\omega t + \varphi)

The above equation is the solution of differential equation of SHM and is the expression for the displacement of the particle at time t.

Velocity of the particle executing SHM

If the initial position from where time is measured is the mean position, then φ=0\varphi = 0

Thus x=asin(ωt+φ)x = asin(\omega t + \varphi) . The velocity of the particle at a given instant of time t is given by differentiating the above equation, i.e.

dxdt=aω  cosωt\frac{dx}{dt} = a\omega \; cos\omega t     or    \; \; or \; \; dxdt=aw1sin2ωt\frac{dx}{dt} = aw\sqrt{1 - sin^2 \omega t}

As we know,   sinωt=xA\; sin\omega t = \frac{x}{A},   \; we have, dxdt=aω1x2a2\frac{dx}{dt} = a\omega\sqrt{1 - \frac{x^2}{a^2}}     or    \; \; or \; \; dxdt=aωa2x2a2\frac{dx}{dt} = a\omega\sqrt{\frac{a^2 - x^2}{a^2}}

Thus the velocity of the particle is:-   \; v=dxdt=aωa2x2v = \frac{dx}{dt} = a\omega\sqrt{a^2 - x^2}

Note: At the extreme position of oscillation, when x=ax=a , v=0v=0. At the mean position, x=0x=0, thus vmax=ωav_{max} = \omega a. Thus vv is maximum at mean position and zero at extreme position.

Acceleration of the particle executing SHM

The displacement of the particle is given by x=asin(ωt+φ)x = asin(\omega t + \varphi). If the particle starts from mean position when t = 0, then initial phase φ=0\varphi = 0 . Thus the above equation is

x=asinωtx = asin\omega t

On Differentiating we get,

dxdt=aωcosωt\frac{dx}{dt} = a\omega cos\omega t

Differentiating again, we get   \; d2xdt2=aω2sinωt=aω2(xa)\frac{d^2x}{dt^2} = -a\omega^2 sin\omega t = -a\omega^2\left(\frac{x}{a}\right)

We know,   sinωt=xa\; sin\omega t = \frac{x}{a}

or the acceleration   d2xdt2=a=ω2x\; \frac{d^2x}{dt^2} = a = -\omega^2 x.

This gives the expression for the acceleration of the particle executing SHM.

Note: At the mean position, when x=0x = 0, a=0a = 0. Also at the extreme position x=ax = a, then amax=ω2aa_{max} = -\omega^2 a i.e. a is maximum at the extreme position.

Time period of a particle executing SHM

The angular frequency of the particle executing SHM is given by ω=2πf\omega = 2\pi f where ff is the frequency. As f=1Tf=\frac{1}{T}, where TT is the time period of SHM, we get ω=2πT\omega = \frac{2\pi}{T} or ,

T=2πωT = \frac{2\pi}{\omega}

This equation can be written as:- T=2π1ω2      —- equation 1T=2\pi \sqrt{\frac{1}{\omega^2}}\; \; \; \text{---- equation 1}

We know, w2=axw^2 = \frac{a}{x}

So Equation - 1 becomes,

T=2πxaT = 2\pi \sqrt{\frac{x}{a}}

As a=(km)xa = \left(\frac{k}{m}\right)x, and a=ω2xa = \omega^2x

Also we have assumed above ω2=km\omega^2 = \frac{k}{m}

leading to T=2πmkT=2\pi \sqrt{\frac{m}{k}}

Energy of SHM

Simple Harmonic Motion

Consider a particle executing SHM represented by y=asin(ωt+φ)y=asin(\omega t+\varphi). The velocity of the particle is v=ωA2ω2v=\omega\sqrt{A^2-\omega^2} and its acceleration is a=ω2xa=-\omega^2x.

The energy of the particle is the sum of its kinetic and potential energies. The particle having a displacement x is further moved through a small distance dx, then the work done:-

dW=F×dx=ma×dxdW = -F \times dx = -ma \times dx

As a=ω2xa = -\omega^2x, the work done is dW=m(ω2x)×dxdW= -m(-\omega^2x) \times dx

or

dW=mω2xdxdW = m\omega^2xdx

Total work done in moving the particle from 0 to x is given by integrating the above equation,

dW=0xmω2xdx\int dW = \int_0^x m\omega^2xdx

or

Ep=W=12mω2x2E_p = W = \frac{1}{2}m\omega^2x^2

This expression gives the potential energy EpE_p of the particle.

The kinetic energy of the particle is EK=12mv2E_K = \frac{1}{2}mv^2.

As v=ωA2x2v=\omega\sqrt{A^2-x^2}

Kinetic Energy becomes:- EK=12mω2(A2x2)E_K = \frac{1}{2}m \omega^2(A^2 - x^2)

The total energy of the particle is E=EP+EKE=E_P + E_K

  E=12mω2x2+12mω2(A2x2)\therefore \; E = \frac{1}{2}m\omega^2x^2 + \frac{1}{2}m \omega^2(A^2 - x^2)

So, E=12mω2A2\: E = \frac{1}{2}m\omega^2A^2     or    \; \; or \; \; E=12m(2πf)2A2\: E = \frac{1}{2}m(2\pi f)^2A^2     or    \; \; or \; \; E=2π2mf2A2E=2\pi^2 m f^2 A^2

Average Values of Kinetic and Potential energy of SHM

SHM

Suppose a particle of mass mm executes SHM of period TT. The displacement of the particles at any instant t is given by, x=Asin(ωt+θ)x = Asin(\omega t + \theta) and velocity is given by, v=dxdt=ωAcos(ωt+θ)v = \frac{dx}{dt} = \omega A cos(\omega t + \theta)

Instantaneous Kinetic Energy EKE_K is given by:-

EK=12mv2=12mω2A2cos2(ωt+θ)E_K = \frac{1}{2}mv^2 = \frac{1}{2}m\omega^2A^2cos^2 (\omega t + \theta)

if TT is time period, then

Average K.E. = 1T0T12mω2A2cos2(ωt+θ)dt\frac{1}{T}\int_0^T{\frac{1}{2}m\omega^2A^2cos^2 (\omega t + \theta)dt}

=mA2ω22T0Tcos2(ωt+θ)dt= \frac{mA^2\omega^2}{2T}\int_0^T{cos^2(\omega t + \theta)dt}

=mA2ω22T0T12[1+cos2(ωt+θ)]dt= \frac{mA^2\omega^2}{2T}\int_0^T\frac{1}{2}[1 + cos2(\omega t + \theta)]dt

=mA2ω24T[0Tcos2(ωt+θ)dt]= \frac{mA^2\omega^2}{4T}\left[\int_0^T{cos2(\omega t + \theta)dt}\right]

=mA2ω24TT= \frac{mA^2\omega^2}{4T}T

=14mA2ω2= \frac{1}{4}mA^2\omega^2

Instantaneous Potential Energy EPE_P is given by:-

EP=12kx2=12kA2sin2(ωt+θ)E_P = \frac{1}{2}kx^2 = \frac{1}{2}kA^2sin^2 (\omega t + \theta)

Average P.E. = 1T0T12kA2sin2(ωt+θ)dt\frac{1}{T}\int_0^T{\frac{1}{2}kA^2sin^2(\omega t + \theta)dt}

=kA22T0T12[1cos2(ωt+θ)dt]=\frac{kA^2}{2T}\int_0^T{\frac{1}{2}[1 - cos2(\omega t + \theta)dt]}

=kA24T[0Tdt0Tcos2(ωt+θ)dt]=\frac{kA^2}{4T}\left[\int_0^T{dt} - \int_0^T{cos2(\omega t + \theta)dt}\right]

=kA24TT=14kA2=\frac{kA^2}{4T}T = \frac{1}{4}kA^2

We know, k=mω2k = m\omega^2

  \therefore \; Average P.E. = 14mA2ω2\frac{1}{4}mA^2\omega^2

Thus, Total Energy = EK+EP=12mA2ω2E_K + E_P = \frac{1}{2}mA^2\omega^2

Thus it is clear that the average kinetic energy of a SHM is equal to the average potential energy and is equal to half the total energy.

Total energy of the oscillating particle is the same at every point of oscillation

Simple Harmonic Motion

The expression for kinetic energy is EK=12mω2(A2x2)      —- equation 1E_K = \frac{1}{2}m\omega^2(A^2 - x^2)\; \; \; \text{---- equation 1}

and potential energy expression is Ep=12mω2x2      —- equation 2E_p = \frac{1}{2}m\omega^2x^2\; \; \; \text{---- equation 2}

The total energy at any point of oscillation is

E=EP+EK=12mw2A2      —- equation 3E = E_P + E_K = \frac{1}{2}mw^2A^2\; \; \; \text{---- equation 3}

  • At the extreme position, x=Ax=A and thus from equation1equation - 1 kinetic energy is zero (as the velocity is also zero). Thus EK=0E_K = 0. Also from equation2equation - 2 As x=Ax=A, at the extreme position, potential energy is EP=12mω2A2E_P = \frac{1}{2}m\omega^2A^2

    Total energy E=EP+EK=12mω2A2    —- equation 4E = E_P + E_K = \frac{1}{2}m\omega^2A^2\; \; \text{---- equation 4}

  • At the mean position, kinetic energy is maximum as the velocity is maximum. Also as x=0x=0 at mean position, from equation1  ,equation - 1\;, EK=12mw2A2E_K = \frac{1}{2}mw^2A^2

    and as x=0x=0, at the mean position, from equation2,equation-2\:, EP=0E_P = 0.

Thus total energy E=EP+EK=12mω2A2      —- equation 5E = E_P + E_K = \frac{1}{2}m\omega^2A^2\; \; \; \text{---- equation 5}

Thus from equations3,4and5equations - 3,4\: and \:5 it is clear that total energy remains same at every point of oscillation.

Numericals on SHM

How's article quality?

Last updated on -

Page Contents